LEGAL CONSCIOUSNESS: STRUCTURE, COMPOSITION AND TYPES (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, the question of the consciousness that forms the basis of society and the legal consciousness that has one fear of it is philosophically conceived. A brief pause is made on the content, structure and types of legal consciousness. Today, it is difficult to tassavur a Democratic state with a legal unconscious, for this reason, the study of the essence of the content of legal consciousness is an important issue.